Effects of α-Mangostin-Loaded Self-Nanoemulsion (MG-SNE) and Physical Exercise on The Reduction of Waist Circumference in Wistar Rats - Andreas Arie Setiawan; Sugiri Sugiri; Awal Prasetyo; Eirin Yovita Kurniawan; Dominikus Evano Putra (RSUP Dr. Kariadi, 2024)
BACKGROUND : Waist circumference (WC) is a marker of intra-abdominal adipose tissue and a risk factor for cardiometabolic disease. A higher risk of coronary heart disease was associated with an increased WC. Garcinia mangostana Linn's anti-inflammatory activity would reduce abdominal fat deposition and WC. Additionally, Garcinia mangostana Linn's potential would increase in nanotechnology. AIMS : To demonstrate that WC in Wistar rats induced by an atherogenic diet can be decreased by α-Mangostin-loaded self-nanoemulsion (MG-SNE) treatment combined with physical activity. METHOD : Experimental research with Randomized Control Trial design using a total sample of 15 male white rats (Rattus novergicus strain Wistar) weighing 300 grams and aged between 6 and 8 weeks, split into 3 groups given physical exercise for 8 weeks along with 3 different doses of medication (group K received Atorvastatin 1.44 mg once; group P1 received Garcinia mangostana Linn pericarp extract, at a dose of 800 mg/kg, divided into 3 administrations; and group P2 received MG-SNE 50 mg/kg once). Waist circumference was measured using a metline, before and after treatment. RESULT : WC decreased in Groups K, P1, and P2, with deltas of -5.00±21.21 mm, -12.50±24.75 mm, and -17.50±12.58 mm. The greatest decrease in WC was P2. There was no significant difference, according to the paired test between the pre-test and posttest in all groups. The p value >0.05 was determined to indicate that there were no significant differences between the groups. CONCLUSION : WC in Wistar rats induced by an atherogenic diet can be decreased by MG-SNE treatment combined with physical exercise.